Workplace-based learning: An industry perspective - Ziegler, R.; Chipanga, T.; Magoda, C. (South African Journal of Higher Education, 2020)
Workplace-based learning (WPBL) is a compulsory component of the Mechanical Engineering undergraduate qualification at a South African university of technology. The Mechanical Engineering students spend a compulsory period of 12 months in industry as part of their undergraduate diploma. However, in response to a national call for curricula revision from the Council on Higher Education (CHE) to align qualifications to the Higher Education Qualifications Sub-Framework (HEQSF), South African higher education institutions embarked on restructuring their qualifications. As a result, the new HEQSF aligned Diploma in Mechanical Engineering (NQF 6) now requires students to spend a reduced period of six months in industry. Given the importance of WPBL in the undergraduate programme, this paper focuses on the new reduced period for WPBL and how industry partners view this change. This study draws on data generated through the use of structured questionnaires. One of the outcomes of this study is that industry partners emphasise the importance of the time that students spend in industry and that a reduction in such time will negatively impact on student workplace learning. The perspectives expressed by the industry partners open up avenues for follow-up studies in this regard.